Fabrication of granular foam glass aggregates from soda lime silicate glass waste - SOOKSAEN, Pat; PRAKAISRI, Phumin; TEERAPATPANID, Pattraporn; PUATHAWEE, Pathompong (Journal of Metals, Materials and Minerals, 2023)
Granular foam glass aggregates were fabricated from a soda lime silicate glass waste which utilized crude glycerol as a foaming agent and sodium silicate as a binder. The granulation and the foaming process were carried out by a granulator and an electric rotary furnace. The study investigated at first the foaming behavior of different foam glass formulations at various sintering temperatures. Three compositions were formulated which utilized glass powder at 85 wt%, 90 wt%, and 95 wt%, respectively. Sintering was carried out at temperatures from 800℃ to 1200℃ to evaluate for the foaming and melting characteristics. Foam glass with 90% glass powder showed overall uniform pore size distribution and small pores at 800℃ to 900℃ while heating above 1000℃ resulted in sample distortion caused by glass melting and the collapse of foam glass structure. Foam glass composition with 90% glass powder was selected for the fabrication of foam glass granules at the sintering temperatures of 850℃ and 900℃ in rotary furnace. The best result was obtained at 850℃ where the granules did not melt and stick together whereas at 900℃ glass melting on the surface of the foam glass granules occurred significantly.